2014
DOI: 10.2337/dc14-0155
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D Supplementation and the Effects on Glucose Metabolism During Pregnancy: A Randomized Controlled Trial

Abstract: OBJECTIVEVitamin D deficiency in pregnancy is associated with an increased risk of gestational diabetes mellitus (GDM) and neonatal vitamin D deficiency. We conducted a doubleblind, randomized controlled trial of low-dose (LD) versus high-dose (HD) vitamin D supplementation to investigate the effects of vitamin D supplementation on glucose metabolism during pregnancy. RESEARCH DESIGN AND METHODSWomen with plasma 25-hydroxyvitamin D (25OHD) levels <32 ng/mL before 20 weeks' gestation were randomized to oral vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 40 publications
7
93
2
3
Order By: Relevance
“…1). We excluded 27 studies, mainly because the comparisons were among different doses of vitamin D without a placebo or control group [7[15], [24], [35], [40], [45], [51], [55], [57], [58], [29], [64], [65], [68]. Also, four trials were not randomised [2], [12], [14], [33] and three were done in pregnant women with chronic conditions [3], [4], [20].…”
Section: Resultsmentioning
confidence: 99%
“…1). We excluded 27 studies, mainly because the comparisons were among different doses of vitamin D without a placebo or control group [7[15], [24], [35], [40], [45], [51], [55], [57], [58], [29], [64], [65], [68]. Also, four trials were not randomised [2], [12], [14], [33] and three were done in pregnant women with chronic conditions [3], [4], [20].…”
Section: Resultsmentioning
confidence: 99%
“…In a double-blind, randomized controlled trial of 54 women with GDM, treatment with two doses of 50 000 IU vitamin D had beneficial effects on fasting glucose and insulin resistance compared with placebo, although it should be noted that these parameters differed between the treatment arms at baseline (37). Most recently, a trial in which 179 women with vitamin D deficiency were randomly assigned to either high-dose or standard vitamin D supplementation from mean 14 weeks' gestation onward found no effect on glucose levels at the OGTT at 26 -28 weeks' gestation (38). In the context of this modest conflicted literature, the current study raises the possibility that previous trials may have failed to detect a robust effect of vitamin D supplementation on glucose metabolism because they were not performed in the specific patient population that might most benefit from this intervention-namely, women whose 25-OH-D levels are unable to suppress PTH.…”
Section: Discussionmentioning
confidence: 94%
“…In Europe, a randomized controlled trial, for preventive measures against the development of GDM in overweight and obese women, is exploring the potential effectiveness of VD supplementation on the risk of developing GDM combined by lifestyle [72]. In contrast, in Australia, a double-blind, randomized controlled trial of low vs. high dose of VD supplementation, concluded that high dose does not improve glucose levels in pregnancy [73].…”
Section: Treating Vitamin D Deficiency In Pregnancymentioning
confidence: 93%